The relationship of learning experiences on the human respiratory system with health literacy and perspective on the dangers of smoking among students in class XI SMAN 1 Godean - Prihatini, Woro; Pertiwi, Kartika Ratna (Universitas Negeri Yogyakarta, 2026)
Health literacy is an important literacy for today’s youth. Health literacy is formed through their learning experiences at school and in the surrounding environment. This study aims to 1) determine the level of learning experience on the human respiratory system, 2) determine the level of health literacy on the human respiratory system, 3) determine students’ perspectives on the dangers of smoking, 4) determine the relationship between learning experience on the human respiratory system and health literacy levels, and 5) determine the relationship between learning experience on the human respiratory system and perspectives on the dangers of smoking among eleventh-grade students of SMAN 1 Godean. This study is a correlational study with quantitative analysis. The sample comprised 125 eleventh-grade students from SMAN 1 Godean, obtained through simple random sampling. The research instruments used were a Likert-scale questionnaire for the learning experience and student perspective variables, a multiple-choice test for the health literacy variable, and an interview guide. Data analysis techniques included descriptive statistics, normality tests, linearity tests, cross-tabulation and correlation tests, and Spearman’s rank correlation test. The results showed that students’ learning experiences were predominantly in the moderate category (48%). Students’ health literacy related to the respiratory system was predominantly in the moderate category (44%). Students’ perspectives on the dangers of smoking were predominantly in the moderate category (40%). Based on the results of the correlation test, there was a positive and significant relationship between learning experiences and students’ health literacy related to the human respiratory system, with a significance value of 0.002 and a correlation coefficient of 0.271. In addition, no significant relationship was found between learning experiences about the human respiratory system and students’ perspectives on the dangers of smoking, with a significance value of 0.250 and a correlation coefficient of 0.104.